1995
DOI: 10.1108/02635579510088128
|View full text |Cite
|
Sign up to set email alerts
|

The effect of discretion, outcome feedback, and process feedback on employee job satisfaction

Abstract: Japanese production techniques and management have been the subject of numerous studies. This research has focused on a variety of areas such as technology, product design and development, process design and development, culture, and personnel management. These studies have made significant contributions to their fields by enhancing our understanding of the way these systems operate, on the one hand, and the ways to improve/fine-tune these systems on the other.An interesting aspect of these systems is employee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…While pay has been considered an external function, other factors (factors of job characteristics) have been defined as internal factors (Rose, 2003). Mcafee et al (1995) investigated effects of discretion, outcome feedback and process feedback on employee job satisfaction. They found that providing discretion and outcome feedback alone does not improve employee satisfaction.…”
Section: Effecting Factors Of Employee Satisfactionmentioning
confidence: 99%
“…While pay has been considered an external function, other factors (factors of job characteristics) have been defined as internal factors (Rose, 2003). Mcafee et al (1995) investigated effects of discretion, outcome feedback and process feedback on employee job satisfaction. They found that providing discretion and outcome feedback alone does not improve employee satisfaction.…”
Section: Effecting Factors Of Employee Satisfactionmentioning
confidence: 99%
“…(DiBerardinis, 1978). Satisfaction as a part of work quantity or quality (Das, 1986; McAfee and Quarstein, 1995; Orpen, 1979). Not in English (Erdemli et al., 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Satisfaction as a part of work quantity or quality (Das, 1986; McAfee and Quarstein, 1995; Orpen, 1979).…”
Section: Methodsmentioning
confidence: 99%
“…Temuan ini sesuai dengan Robbins (2001b:97), McAfee et al (1995), Ghiselli and Brown dalam As'ad (2003:112), As'ad (1995:103), Luthans (2006:246) Perlu dikembangkan kajian akademis yang spesifi k atas sistem manajemen yang akan diterapkan, agar kinerja perusahaan secara keseluruhan sukses menuju excellent corporate performances.…”
Section: Pengaruh Kepuasan Kerja Terhadap Kinerja Karyawanunclassified